2017
DOI: 10.1167/17.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Do twins share the same dress code? Quantifying relative genetic and environmental contributions to subjective perceptions of “the dress” in a classical twin study

Abstract: The phenomenon of contrasting color perceptions of "the dress" photograph has gained scientific interest. The mechanism underlying why individuals differ is yet to be fully explained. We use the powerful twin model design to ascertain the relative contribution of genetic and environmental factors on perception variation. A sample of 466 twins from the British TwinsUK registry were invited to report what color they saw in a standard image of the dress in standard illumination. The mean age of the participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Using an unconstrained colour term choice methodology in the current study, we report an approximately even split between B&B and W&G viewers (similar to Aston & Hurlbert, 2017;Chetverikov & Ivanchei, 2016;Hesslinger & Carbon, 2016;Karlsson & Allwood, 2016;Schlaffke et al, 2015;Vemuri et al, 2016;Winkler et al, 2015). We further confirm that several individuals reported seeing the ambiguous Dress picture as B&Br (Aston & Hurlbert, 2017;Lafer-Sousa et al, 2015;Mahroo et al, 2017;Wallisch, 2017;Witzel et al, 2017).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Using an unconstrained colour term choice methodology in the current study, we report an approximately even split between B&B and W&G viewers (similar to Aston & Hurlbert, 2017;Chetverikov & Ivanchei, 2016;Hesslinger & Carbon, 2016;Karlsson & Allwood, 2016;Schlaffke et al, 2015;Vemuri et al, 2016;Winkler et al, 2015). We further confirm that several individuals reported seeing the ambiguous Dress picture as B&Br (Aston & Hurlbert, 2017;Lafer-Sousa et al, 2015;Mahroo et al, 2017;Wallisch, 2017;Witzel et al, 2017).…”
supporting
confidence: 79%
“…In the initial Internet survey of about three million respondents, 68% of the respondents indicated seeing the ambiguous Dress picture as W&G and 32% of the respondents as B&B in a forced-choice situation (Holderness, 2015). Subsequent studies reported a higher proportion of W&G viewers (Dixon & Shapiro, 2017;Mahroo et al, 2017;Moccia et al, 2016;Wallisch, 2017;Witzel, Racey, & O'Regan, 2017), a higher proportion of B&B viewers (Chetverikov & Ivanchei, 2016;Lafer-Sousa et al, 2015), or an equal split between the two viewer types (Aston & Hurlbert, 2017;Chetverikov & Ivanchei, 2016;Hesslinger & Carbon, 2016;Karlsson & Allwood, 2016;Schlaffke et al, 2015;Vemuri et al, 2016;Winkler, Spillmann, Werner, & Webster, 2015) using forced-choice and free naming paradigms. In studies that went beyond the possibility of two viewer types, mainly using freenaming paradigms to assess the colours of the ambiguous Dress picture, an intermediate variant of the Dress perception emerged -participants reported seeing the Dress as blue and brown/gold (B&Br) (Aston & Hurlbert, 2017;Lafer-Sousa et al, 2015;Mahroo et al, 2017;Wallisch, 2017;Witzel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to predict the color percept from genetic markers were unsuccessful even in very large samples (Sathirapongsasuti, 2015), and even monozygotic twins seem to exhibit a surprisingly high degree of perceptual variability (Mount, 2015), making a purely genetic basis of this phenomenon unlikely. Recent research suggests that the proportion of variance accounted for by genetics is on the order of 33% with the remainder due to environmental factors (Mahroo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some have argued that the individual differences in the perception of the dress are due to hard-wired, sensory differences in perceptual processing. This view is supported by evidence that twins tend to see the colours similarly ( Mahroo et al, 2017 ), and that white-gold seers tend to have larger pupil sizes ( Vemuri, Bisla, Mulpuru, & Varadharajan, 2016 ) and higher macular pigment optical density ( Rabin, Houser, Talbert, & Patel, 2016 ). Moreover, the observation that the perception of the dress is related to gender and age might also be taken as evidence for hard-wired determinants, such as age-related changes in the eye ( Lafer-Sousa et al, 2015 , Mahroo et al, 2017 , Moccia et al, 2016 , Wallisch, 2017 ).…”
Section: Introductionmentioning
confidence: 89%